2023
DOI: 10.3390/s23031370
|View full text |Cite
|
Sign up to set email alerts
|

An Indoor Location-Based Augmented Reality Framework

Abstract: This paper proposes an indoor location-based augmented reality framework (ILARF) for the development of indoor augmented-reality (AR) systems. ILARF integrates an indoor localization unit (ILU), a secure context-aware message exchange unit (SCAMEU), and an AR visualization and interaction unit (ARVIU). The ILU runs on a mobile device such as a smartphone and utilizes visible markers (e.g., images and text), invisible markers (e.g., Wi-Fi, Bluetooth Low Energy, and NFC signals), and device sensors (e.g., accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…MQTT can facilitate indoor navigation by enabling devices to share information such as sensor data, user information, and location estimates [29][30][31][32]. Jiang et al [33] adopt three major frameworks in their indoor location-based augmented reality framework (ILARF), which implements AR visualization, indoor localization unit (ILU), and context-aware message exchange through the utilization of MQTT protocol containing servers for clients to subscribe and publish IMU data. The localization system is intended for an indoor gym application known as Gym Augmented Reality (GAR), where users can interact virtually and at the same time know each other's whereabouts within the application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MQTT can facilitate indoor navigation by enabling devices to share information such as sensor data, user information, and location estimates [29][30][31][32]. Jiang et al [33] adopt three major frameworks in their indoor location-based augmented reality framework (ILARF), which implements AR visualization, indoor localization unit (ILU), and context-aware message exchange through the utilization of MQTT protocol containing servers for clients to subscribe and publish IMU data. The localization system is intended for an indoor gym application known as Gym Augmented Reality (GAR), where users can interact virtually and at the same time know each other's whereabouts within the application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Methods utilizing markers for AR placement have been explored; however, they entail the inconvenience of physically installing markers, which are impractical for outdoor environments [22]. Additionally, indoor-based approaches lack adequate outdoor application [23]. Although outdoor AR solutions employing GPS have been proposed, the inaccuracies associated with GPS can significantly hinder the precise localization and recognition of objects [24].…”
Section: Introductionmentioning
confidence: 99%
“…Fick et al, 2021) It is therefore observed that AR technologies can improve users' spatial awareness by producing contextually relevant information and visualizations that facilitate spatial orientation and updating. Overlaying digital markers or clues on real-world imagery improves users' situational awareness and supports effective navigation strategies such as landmark-based navigation and route planning(Jiang & Subakti, 2023;Khan et al, 2022).Challenges and Research in Health Sciences: A Multidisciplinary Approach Neuropsychology, Augmented Reality and Virtual Reality in the context of ERPI -Innovative approaches to the well-being of the elderly In summary, the different studies related to the cognitive functions used in AR therapy sessions provide valuable information about the potential of AR technology as a tool for cognitive improvement. Based on the perspectives of the referenced authors, there are several key points that highlight the various benefits of using AR for cognitive function: Increased engagement and immersion AR interventions provide immersive and interactive experiences that engage users in cognitive tasks and activities, fostering active participation and engagement in spatial, memory, executive function, and attention processes.…”
mentioning
confidence: 99%